Chromium removal from tannery wastewaters with a strong cation exchange resin and species analysis of chromium by MINEQL - Kocaoba, Sevgi; Cetin, Gulten; Akcin, Goksel (NATURE PORTFOLIO, 2022)
Chromium (III) salts are highly applied for tanning purpose in tannery industries. The purpose of this study was removal and recovery of chromium(III) from tannery wastewater with a strong cation exchange resin. For this purpose, Amberlite 252 ZU was chosen as a strong cation exchange resin. In the first part of this study, The MINEQL+ computer program was applied depending on the optimum concentration and pH for determining Cr species in aqueous solutions. The second part of the work consists of measuring the exchange equilibrium of H+ ions and Cr(III) ions. Therefore, solutions containing fixed amounts of chromium were brought into contact with different amounts of resins. The evaluation of the obtained equilibrium parameters was done by surface complexing theory. Retention and regeneration steps were successfully performed in the column without any significant change up to 10 cycles. Efficiency was between 90 and 98% in removal studies, and between 81 and 92% in recovery studies. The results showed that a strong cation exchange resin Amberlite 252 ZU can be successfully used for chromium removal and recovery.
Keywords: COMPLEX-FORMATION MODEL; SURFACE COMPLEXATION; ION-EXCHANGE; HEXAVALENT CHROMIUM; AQUEOUS-SOLUTION; HEAVY-METALS; ADSORPTION; EQUILIBRIA; RECOVERY; CR(III); Science & Technology - Other Topics